Evaluation Of Serang City Regional Regulation Number 17 Of 2010 Concerning Local Taxes in Serang City (Case Study of Hotel Tax on Boarding Houses) - Ishlahati; Juliannes Cadith; Ipah Ema Jumiati (International Journal of Social Sciences Review, 2022)
The focus of this research is the evaluation of Serang City Regional Regulation Number 17 of 2010 concerning Local Taxes, especially Hotel Taxes on Boarding Houses in Serang City. In this evaluation, there are several problems in the implementation of the policy, such as the number of boarding houses with more than ten rooms not recorded by the Regional Revenue Agency (Regional Revenue Agency (Bapenda) Kota Serang, which makes boarding house owners with hotel tax categories not registered as taxpayers; Low level of awareness of hotel taxpayers on the boarding house of Serang City; The weak role of the government in approaching the taxpayer or going directly to the field; and the lack of socialization carried out by Regional Revenue Agency (Bapenda) Serang City. The theory used is the evaluation theory developed by Daniel Stufflebeam consists of four stages of evaluation aspects, namely CIPP. The qualitative descriptive method provides an overview of data analysis techniques using the Irawan model. The result of this study is that the implementation of the hotel tax policy on boarding houses in Serang City has not been running optimally. The hotel tax rate onboarding houses at a rate of 10% is still felt objection by the hotel taxpayer on the boarding house to make the taxpayer in arrears to pay the local tax. The lack of human resources, which is an important element in the success of policies that have data collection, registration, reporting, and evaluation of hotel taxes on boarding houses, is still experiencing a shortage. The available facilities and infrastructure are still inadequate. Socialization is still not optimal and thorough, so information about hotel tax policies on boarding houses is not conveyed properly, and weak enforcement of sanctions. Not yet optimally the contribution of hotel taxes on boarding houses to the Local Own-Source Revenue of Serang City Area from the regional tax sector.